Competition, marketisation, public services and public ethics - Harris, Tony (1999)
The topic I address provides an embarrassment of scope. At the same time, it allows the development of a theme that is worthwhile discussing. When in the public sector is it worthwhile to import private sector concepts, principles and practices and when would the adoption of a private sector model be injurious to the state's constituents? The theme is worthwhile discussing, in part because some of Australia's jurisdictions appear to be adopting what they consider to be private sector practices, without an adequate framework to guide them. Because there is no proper framework, mistakes are made which could have been avoided. There is also some evidence that the public is uneasy about the loss of `public' from the term public services. It would not be in the public's own interests to resist, for no good reason, the adoption of private sector principles where that would allow more cost-effective services. The topic also allows a discussion on the influence on public sector ethics of the trend to place senior public servants on contracts that can be disposed of without a reason or prospect of appeal. - Reproduced
Keywords: Ethics; Public administration; Civil service